CULTURAL AND SOCIO-ECONOMIC FACTORS AFFECTING THE FORMATION OF LEADERSHIP IN ACHIEVING SUSTAINABLE MANAGEMENT: IN THE CONTEXT OF UKRAINE - Liudmyla Batsenko; Roman Halenin (Agora International Journal of Economical Sciences (AIJES), 2024)
New challenges for leaders in the field of sustainable management are awareness of cultural and socio-economic factors in the practice of organizational development and organizational change. The purpose of the article is to contribute to the existing body of knowledge through a systematic study of the influence of culture and socio-economic factors on the formation of leadership in the context of sustainable management. The research methodology includes a literature review, analysis of cultural and socio-economic aspects that influence the formation of leadership for sustainable management. The study is based on the analysis of empirical data obtained through questionnaires. The research results highlighted the impact of culture on leadership in Ukraine, some age differences in the perception of culture as an important element of the triad "sustainable management - leadership - cultural and socio-economic factors", the importance of socio-economic factors and the crucial role of education in the development of leadership for sustainable management. Leaders must adapt their approaches to management, considering cultural aspects, economic conditions and societal demands.
Keywords: 330